Victim, international idealism and neopunitivismo in the Criminal Law (2013)
This paper intends to explain the way in which the rights of the victims have caused neopunitivism, emphasizing in the Inter-American Court of Human Rights, and also, give reasons for which it is understood that this trend represents a revalidation of the